Evaluasi Aktivitas Diuretik Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa bilimbi) Sebagai Diuretik Alami: Kadar Natrium, Kalium, dan pH Urin - ANDRIYANTO ANDRIYANTO; PONIMAN PONIMAN; ABADI SUTISNA; WASMEN MANALU (Fakultas Farmasi Universitas Pancasila, 2013)
Previous study reported that Averrhoa bilimbi fruits had a potency as a natural diuretic. This research was conducted to examine the effects of ethanolic extract of Averrhoa bilimbi fruits on diuretic activity, urine sodium and potassium concentrations, and pH of urine male rats Sparague-Dawley. Fifteen rats were divided into 5 groups and 3 replications. Group 1 was given saline (negative control), group 2 was given furosemide 20 mg/kg bw (positive control), group 3 was given extract of Averrhoa bilimbi 0.44 g/kg bw, group 4 was given extract of Averrhoa bilimbi 0.88 g/kg bw, group 5 was given extract of Averhoa bilimbi 1.75 g/kg bw. Averrhoa bilimbi extract, saline, and furosemide were administred orally. The diuretic activity was determined by measuring cumulative urine volume for 10 hours post administration. The result showed that the extract of Averrhoa bilimbi at dosages of 0.88 and 1.75 g/kg bw increased sodium and potassium excretion by 18-36% and 22-27%, respectively. On the other hand, the increased diuretic activity and sodium and potassium excretion dramatically decreased urine pH. It was concluded that extract of Averrhoa bilimbi at dosages of 0.88 and 1.75 g/kg bw increased diuretic activity with enchanced sodium and potassium excretion in urine. The extract of Averrhoa bilimbi cosisted of alkaloid, flavonoid, and saporin that were assumed to have synergic activities as natural diuretics.